Germanium recovery by catechol complexation and subsequent flow through membrane and bead‐packed bed column. Issue 8 (11th December 2012) - Takemura, Hiroaki; Morisada, Shintaro; Ohto, Keisuke; Kawakita, Hidetaka; Matsuo, Yoshiyasu; Fukuda, Daisuke
Abstract BACKGROUND Ion‐exchange has been a powerful tool for metal recovery. Germanium has been recovered using the commercially available N‐methylglucamine resin. To treat waste‐water from solar panel displays a method to separate selectively germanium from silicate ion was required. A novel recovery of germanium is proposed in which germanium is complexed with catechol in solution and the complex solution flowed through a membrane or bead‐packed bed. RESULTS By changing pH, germanium was complexed with catechol, 3‐methylcatechol and 4‐nitrocatechol in solution and the solution was adsorbed on the membrane in a batch mode, demonstrating that catechol exhibited a high adsorption performance in neutral pH. In a continuous system, the membrane achieved faster adsorption of the germanium complex than a bead‐packed bed. CONCLUSION The high‐speed recovery of germanium was due to the transport to the vicinity of quaternary amino group in the membrane via convection. A germanium solution containing silicate ions was passed through the membrane system, resulting in highly selective recovery of germanium ion. © 2012 Society of Chemical Industry